Migration and remittances in Kazakhstan: Survey technical report - Barbara Dietz; Kseniia Gatskova (Osteuropa-Institut Regensburg, 2011)
This paper presents the technique of a household survey on migration and remittances in Kazakhstan which was conducted between October and December 2010. Based on a random route sampling strategy 2,227 households were interviewed in the cities Almaty, Astana, Karaganda and Pavlodar. The core part of this paper is devoted to a discussion of the survey's methodology and the questionnaire design. Furthermore, it is shown how interviewer training and quality control were implemented. Finally, a short overview over the characteristics of respondents and surveyed households is given.
Keywords: C83; R23; 330; Kazakhstan; survey methods; internal migration